Extensional shear zones as imaged by reflection seismic lines: the Larderello geothermal field (central Italy) - Brogi, Andrea; Lazzarotto, Antonio; Liotta, Domenico; Ranalli, Giorgio (Tectonophysics, 2003)
The Larderello geothermal field is located in the Inner Northern Apennines, in an area which has been subject to extension since the Early Miocene. The latest extensional episode (Pliocene–Present) has resulted in the formation of NW-trending, NE-dipping listric normal faults, whose geometry is controlled down to ∼3 km by borehole data. In this paper, we integrate a new interpretation of seismic reflection lines with existing seismic, field, and borehole data to analyse the relations among listric normal faults, the top of the brittle–ductile transition, and the migration of geothermal fluids. In accordance with previous interpretations, we consider the strong reflector (K-horizon) marking the top of the reflective mid-lower crust, and located at a depth of 3–5 km in the geothermal area, to represent the top of the brittle–ductile transition. Its reflectivity most probably derives from the presence of overpressured fluids. We identify three main NW-trending, NE-dipping extensional brittle shear zones, showing listric geometry and soling out in the vicinity of the K-horizon. The latter appears to be dislocated in correspondence of the soling out of the shear zones. These shear zones, because of the associated intense fracturing, represent the most natural channels of upward migration of geothermal fluids from the magmatic sources located below the K-horizon. We suggest that these two conclusions—that listric normal faults root at or near the brittle–ductile transition, and that they act as preferential upward migration paths for magmatic fluids—may be of general validity for geothermal fields located in extensional settings.